2006
DOI: 10.1137/050624522
|View full text |Cite
|
Sign up to set email alerts
|

Variable Exponent, Linear Growth Functionals in Image Restoration

Abstract: We study a functional with variable exponent, 1 ≤ p(x) ≤ 2, which provides a model for image denoising, enhancement, and restoration. The diffusion resulting from the proposed model is a combination of total variation (TV)-based regularization and Gaussian smoothing. The existence, uniqueness, and long-time behavior of the proposed model are established. Experimental results illustrate the effectiveness of the model in image restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
717
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,365 publications
(721 citation statements)
references
References 33 publications
1
717
0
3
Order By: Relevance
“…For deep results in weighted Sobolev spaces with applications to partial differential equations and nonlinear analysis we refer to the excellent monographs by Drabek, Kufner and Nicolosi [13], Hyers, Isac and Rassias [21], Kufner and Persson [25], and Precup [34]. We also refer to the recent works by Diening [11], Ruzicka [36] and Chen, Levine and Rao [8] for applications of Sobolev spaces with variable exponent in the study of electrorheological fluids or in image restoration.…”
Section: Introduction and Auxiliary Resultsmentioning
confidence: 99%
“…For deep results in weighted Sobolev spaces with applications to partial differential equations and nonlinear analysis we refer to the excellent monographs by Drabek, Kufner and Nicolosi [13], Hyers, Isac and Rassias [21], Kufner and Persson [25], and Precup [34]. We also refer to the recent works by Diening [11], Ruzicka [36] and Chen, Levine and Rao [8] for applications of Sobolev spaces with variable exponent in the study of electrorheological fluids or in image restoration.…”
Section: Introduction and Auxiliary Resultsmentioning
confidence: 99%
“…A mathematical analysis was also done for such problems by Acerbi and Mingione [1,2] and by Acerbi et al [3]. In [27], some nonlinear parabolic problem proposed by [17] was studied in a weak formulation and an existence result for weak solutions was established. Antontsev and Shmarev studied parabolic equations involving anisotropic p(·, ·)-Laplace operators with log-Hölder continuous (x, t)-dependent exponents and proved the existence, uniqueness, extinction in finite time and blow-up of solutions in [7][8][9][10].…”
Section: G Akagi and K Matsuuramentioning
confidence: 99%
“…The constant exponent p(·) ≡ p is particularly known to have a threshold between two drastically different types of nonlinear diffusion, and moreover, the limit of p → ∞ exhibits a peculiar phenomena called fast/slow diffusion. Parabolic equations involving the p(·)-Laplacian have been proposed in the study of image restoration (see [17]) as well as in some model of electrorheological fluids (see [19,21,34]). A mathematical analysis was also done for such problems by Acerbi and Mingione [1,2] and by Acerbi et al [3].…”
Section: G Akagi and K Matsuuramentioning
confidence: 99%
“…Hence, regularization through TV promotes recovery of edges, which appear as "jumps" or discontinuous parts of the image, and effective noise removal. But studies have revealed that TV formulations favor piecewise-constant solutions, a consequence that generates staircase effects and introduces false edges [16]. Also, TV regularization tends to lower contrast even in noise-free or flat image regions [17].…”
Section: Image Degradation Modelmentioning
confidence: 99%